A Review of eHealth Initiatives: Implications for Improving Health Service Delivery in Nepal - KC, Ashish; Sunny, Avinash K; Poudel, Rajendra Prasad; Basnet, Omkar (Journal of Nepal Health Research Council, 2019)
The aim of this paper is to take stock of the use of information and communication technologies in delivering health services in Nepal and identify bottlenecks in implementation for improving delivery of health services. A descriptive review was conducted from May to September 2016. Data were collected from organizations working on the different thematic areas in health where information and communication technologies was used. Fifteen ongoing eHealth projects were identified in the areas of monitoring and surveillance, electronic health records/electronic medical records, health information system, and telemedicine. Common challenges were addressed, including a lack of funding, infrastructure, electricity and network, and national capacity. Most eHealth projects were not integrated into the national system. Working at a national level to address the challenges, centralizing eHealth projects and developing national policies would ensure to adopt eHealth at a right place and to accelerate eHealth initiatives.Keywords: eHealth; health service delivery;information and communication technologies (ICT); Nepal.